EFFECT OF PRODUCT QUALITY AND BRAND EQUITY ON BUYING INTEREST - Kurniawati, Luciana Mia (Journal of Digital Marketing and Halal Industry, 2019)
This research aims to review the influence of the quality of products and brand equity in a partial and simultaneous against the interest of consumers to buy products fashion zoya. Over the withdrawal of funds the sampling method of uses the method random sampling , by smeru within the of this research is there were thousands of visitors zoya boutique in the stall for as many as 154 respondents in the present study. The results of the study and reason 5 percent significance finds that: (1) product quality has a positive effect on buying interest, (2) brand equity has a positive effect on buying interest, and (3) product quality and brand equity together have a positive and significant effect on buying interest. Keyword : Electronic Quality Service, Electronik Trust, Customer Satisfaction